2021
DOI: 10.1002/adhm.202100090
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra‐Stable, Oxygen‐Supply Nanoprobe Emitting in Near‐Infrared‐II Window to Guide and Enhance Radiotherapy by Promoting Anti‐Tumor Immunity

Abstract: Currently, radiotherapy (RT) is the main method for cancer treatment. However, the hypoxic environment of solid tumors is likely to cause resistance or failure of RT. Moreover, high‐dose radiation may cause side effects to surrounding normal tissues. In this study, a new type of nanozyme is developed by doping Mn (II) ions into Ag2Se quantum dots (QDs) emitting in the second near‐infrared window (NIR‐II, 1000–1700 nm). Through the catalysis of Mn (II) ions, the nanozymes can trigger the rapid decomposition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…However, the low O 2 level in the tumor microenvironment usually leads to cancer radio-resistance or failure of RT. To overcome this dilemma, Wang et al doped Mn 2+ into second near-infrared (NIR-II)-emitting Ag 2 Se quantum dots to endow the system with CAT-like activity [136]. By the catalysis of Mn 2+ in the quantum dots, H 2 O 2 was decomposed into O 2 .…”
Section: Oxygen Supplymentioning
confidence: 99%
“…However, the low O 2 level in the tumor microenvironment usually leads to cancer radio-resistance or failure of RT. To overcome this dilemma, Wang et al doped Mn 2+ into second near-infrared (NIR-II)-emitting Ag 2 Se quantum dots to endow the system with CAT-like activity [136]. By the catalysis of Mn 2+ in the quantum dots, H 2 O 2 was decomposed into O 2 .…”
Section: Oxygen Supplymentioning
confidence: 99%
“…Researchers have fostered nanozymes by doping Mn (II) and Silver Selenide quantum dots particles (Ag2Se QDs) transmitting in the second near-infrared window. These nanozymes are attached with cancer targeting arginine-glycine-aspartate (RGD) tripeptides and polyethylene glycol and built into in vivo nanoformulations for NIR-II imaging-directed radiation treatment of malignancy [21]. Tumor particularity and NIR-II radiating abilities of the nanoprobes empower exact confinement, giving exact RT.…”
Section: Quantum Dots In Medical Applicationsmentioning
confidence: 99%
“…Carboxylated CuInS/ZnS QDs (ZCIS QDs) were added to intraocular lenses by a facial initiation-immersion technique to warm up the lenses and keep the cells from sticking to the lens surface. This technique could assist with regarding cataract development as well as posterior capsule opacification (PCO) [21].…”
Section: Quantum Dots In Medical Applicationsmentioning
confidence: 99%
“…This nanozyme can accurately target TME, and the CAT-like activity of the Mn (II) component can rapidly convert H 2 O 2 into O 2 . [70] Cheng et al reported a cage-like carbon-Mn nanozyme with CATlike activity that catalyzes the production of O 2 from H 2 O 2 in the TME to overcome tumor hypoxia and enhance PDT, coupled with PTT for optimal therapeutic efficacy [90] (Figure 4a). In another report, the researchers used MnO 2 , GOx, and BSA-Chlorine e6 to make MBG.…”
Section: Mn-based Nanozymes With Cat-like Activitymentioning
confidence: 99%